News Briefs. (Computer (00189162), 2014)
Topics include Russian hackers stealing more than 1 billion usernames and passwords, researchers developing a new type of brain-inspired chip, a US judge rejecting a Silicon Valley corporate-collusion settlement, proponents saying that their new networking approach could replace TCP/IP, researchers setting a speed record for data transmission over copper wiring, a "digital tattoo" that unlocks smartphones, a group proposing a new smart-home wireless technology, cloud computing making life difficult for forensics investigators, smart robotic furniture that can assemble and reassemble itself, and a sensor system that will track players' performance during this year's US professional football season.